MANFAAT KEGIATAN KATOLISITAS BAGI PESERTA DIDIK SMPK 3 YOS SOEDARSO, BLITAR - Maharani, Theresia Putri; Wijaya, Albert I Ketut Deni (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
School pastoral is a pastoral activity carried out in the school in order to develop students’ faith and to introduce to them the teachings of the Catholic Church. School pastoral can be done throughout catholicity programs to direct the students to understand better the life of the Christianity.There are many benefits achieved by the students when they are participating in the various catholicity programs offered at the school. However, sometimes the benefits of the catholicity programs are less achieved by the students because they did not deeply involve in such programs. Based on the research background, the researcher then formulated the research problem as the following: to what extent the students can benefits from the catholicity programs offered in the school for their spirituality and personality development and maturity? The aim of the research is to find out to what extent the students can benefits from the school’s catholicity programs. The researcher applied a qualitative method for the study. The results of the research indicated that catholicity programs are so much helping the students to develop better their Christian faith and character.